Working Time Flexibility and Parental 'Quality Time' Spent with Children - Iga Magda; Roma Keister (Institute of Labor Economics (IZA), 2018)
The aim of our paper is to analyse the relationship between working time flexibility and parental time devoted to children. Using data from a large panel survey of Polish households carried out in 2013 and 2014 (Determinants of Educational Decisions Household Panel Survey, UDE) we investigate whether and how various dimensions of working time flexibility affect the amount of time parents spend with their children reading, playing or teaching them new things. We account for employment status of parents, their socio-economic status and social and cultural norms they share. Our results show that employment status of parents and their working time arrangements are not statistically significant for the amount of parental 'quality time' devoted to children. We show that these are parental human and cultural capital and their values that are primary factors determining the amount of parental time investments.
Keywords: J13; J22; J81; 330; working time flexibility; parental time investments; child care; 'quality time with children'